AEROBIC AND ANAEROBIC CAPACITY OF FOOTBALL PLAYERS AS DETERMINANT FOR PROGRAMMING TRAINING WORK - B.Krsmanović; R.Krulanović; Tijana Krsmanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Realization of a sportsman's is affected by all components of his personality, or simply by all spaces of his anthropological status. Most of all, these are his anthropometrical characteristics, motor abilities, functional abilities, cognitive abilities, personality traits, and sociological status. The purpose of this paper is to point out the results and methodological procedures of planning and monitoring training process of football players as a research sample.The purpose of this paper is to point out the results and methodological procedure of planning and monitoring training process of football players who served as a research sample. Due to the complexity of the problem, on one hand, and spatial temporal possibilities on the other, the paper presents results of functional tests for evaluation of functional abilities of football players according toConconi and Shuttle Run Test, as well as methodology procedure of work planning. Programming training work was based on the results of testing senior football players of "Spartak-Zlatibor voda" as a 1st-league club of Serbia.